Innovation and Collaboration in Organizations: A Bibliometric Research - Syamsul Hadi; Nabila Wahyuningtyas; Anggita Putri Rachmawati; Lois Lutria Tang; Ghea Mentariningtyas (INTERNATIONAL JOURNAL OF ECONOMICS AND MANAGEMENT REVIEW, 2023)
Purpose - This article is a bibliometric study of innovation research and internal collaboration in organizations at three levels (i.e., individual, work team, and organization). Design/methodology/approach - This research was conducted using Publish or Perish software and VOS Viewer to analyze 6,356 academic articles from 2000 to 2022 in four aspects: temporal distribution of published papers, the scientific community (country/region/authors cited), intellectual structure (journals) cited/references cited), and research centers. Findings and Discussion – The results show that the number and growth rate of publications at the organizational level is much higher than the other two levels (individual and teamwork). This is based on innovation which is often related to collaboration within the organization. The publications with top three countries for the most publications are the United States, China, and the United Kingdom. The top five most cited authors were identified and listed from the individual, work team, and organizational levels Originality - The author combines innovation and collaboration as an interesting subject because not many have made a review of this material. These findings provide a snapshot and comparison of innovation research in management at three levels namely, individual, work team, and organizational levels, which are useful for researchers and students to understand and explore innovative behavior in organizations from a multilevel perspective.